Huszárok hőstette az 1849. téli hadjáratban a főhadszíntéren: HUSSARS’ FEAT OF ARMS ON THE THEATRE OF WARM, AT WINTER CAMPAIGN IN 1849 - Hermann, Róbert (Közép-Európai Közlemények, 2020)
The study presents the role of the Hungarian hussars in the 1849 winter campaign on the basis of the military reports and award proposals. He speaks separately about Görgei’s battles in northern Hungary, the defensive battles of the Upper Tisza Corps, the January counterattack of Mór Perczel’s corps, the period of Henryk Dembinski’s high command, including the battles at Kápolna, Mezőkövesd and Szolnok.